2020
DOI: 10.3892/ol.2020.12103
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL1 is a potential biomarker for differentiated thyroid cancer diagnosis and recurrence

Abstract: Differentiated thyroid cancer (DTC) is a common type of cancer among women with an increasing worldwide incidence rate. However, there are no specific and sensitive molecular biomarkers for DTC diagnosis or prognosis. Angiopoietin-like protein 1 (ANGPTL1) may be a novel tumor suppressor in lung, breast, colorectal and hepatocellular carcinoma. However, little is known about the influence of ANGPTL1 on the malignant properties of thyroid cancer cells or DTC recurrence in patients. Thus, the present study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…At the same time, there is no relevant research on GC on the effects of LCN1 and ANGPTL1 on GC and its mechanism. However, LCN1 and ANGPTL1 have high therapeutic and diagnostic value in other cancer research [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there is no relevant research on GC on the effects of LCN1 and ANGPTL1 on GC and its mechanism. However, LCN1 and ANGPTL1 have high therapeutic and diagnostic value in other cancer research [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angiopoietin-like protein 1 (ANGPTL1) is a member of ANGPTLs family and known as an anti-angiogenic factor as well as a tumor suppressor. Indeed, ANGPTL1 is down-regulated in several cancers, including lung [ 9 ], thyroid [ 10 ], hepatocellular carcinoma [ 11 ] and colorectal cancer [ 12 ]. ANGPTL1 is implicated in the angiogenesis [ 11 ], metastasis [ 13 ], inflammation [ 14 ], hematopoietic stem cell behavior [ 15 ], lipid metabolism [ 16 ], drug resistance [ 17 ] and cancer progression [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that ANGPTL1 can act as an anti-angiogenic factor and a tumor suppressor [ 28 ]. ANGPTL1 has been reported to suppress migration and invasion in lung, breast and colorectal cancer, acting as a novel tumor suppressor candidate [ 29 ]. For SLC22A18AS, high expression levels are significantly associated with worsening disease progression.…”
Section: Resultsmentioning
confidence: 99%